2020
DOI: 10.1186/s12866-020-01811-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteriophages against virulent Aeromonas hydrophila

Abstract: Background Aeromonas hydrophila is an important water-borne pathogen that leads to a great economic loss in aquaculture. Along with the abuse of antibiotics, drug-resistant strains rise rapidly. In addition, the biofilms formed by this bacterium limited the antibacterial effect of antibiotics. Bacteriophages have been attracting increasing attention as a potential alternative to antibiotics against bacterial infections. Results Five phages against … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…The majority of marine phages are highly host-specific [ 232 , 233 , 234 ], and about 73% lyse only the original host bacterium [ 234 ]. Although phages with a broad host range are hard to find, some examples of virulent phages have shown some promise for therapeutic use in aquaculture, infecting strains of several bacterial species [ 180 , 181 , 217 , 235 , 236 ] and genera [ 92 , 237 ] ( Table S2 ). Liu et al (2020) reported that the isolated phages had a relatively broad infectivity spectrum against A. hydrophila and showed the potential to infect A. veronii , A. caviae and A. bestiarum [ 236 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…The majority of marine phages are highly host-specific [ 232 , 233 , 234 ], and about 73% lyse only the original host bacterium [ 234 ]. Although phages with a broad host range are hard to find, some examples of virulent phages have shown some promise for therapeutic use in aquaculture, infecting strains of several bacterial species [ 180 , 181 , 217 , 235 , 236 ] and genera [ 92 , 237 ] ( Table S2 ). Liu et al (2020) reported that the isolated phages had a relatively broad infectivity spectrum against A. hydrophila and showed the potential to infect A. veronii , A. caviae and A. bestiarum [ 236 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…It was reported that burst sizes are variable in Siphovirus (between 60 and 147 PFU/mL), whereas latent periods and rise times range from 16 to 55 min and 24 to 65 min, respectively [40,41]. Phages have different activities against bacteria, including (i) bacteriostatic activity that stops the bacterial growth, as in Acinetobacter baumannii after 360 min of incubation with phages [42,43], and P. aeruginosa [44]; and (ii) bacteriolytic activity, represented by the reduction in bacterial OD 600 from starting concentration, as in A. baumannii [45] and Aeromonas hydrophila [46]. In this study, phage ZCSE6 presented a bactericidal effect against Salmonella with a significant reduction rate compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, temperature determines the occurrence, viability, and storage of bacteriophages [16]. In the study of Liu., et al [26], the five bacteriophages (W3, G65, Y81, N21, Y71) maintained almost 100% infectivity after be- Knowledge of phage stability is necessary when phages are subjected to industrial processes such as manufacturing medicated feed, where high temperatures and different pH are often used [21].…”
Section: Temperature Stability Of Bacteriophagesmentioning
confidence: 99%